167 Randomized, Double-Blind, Active-Controlled Study of Starting Aripiprazole Lauroxil with 1-Day Initiation in Acutely Ill Patients with Schizophrenia. (April 2020) - Weiden, Peter J.; Claxton, Amy; Du, Yangchun; Yagoda, Sergey; Walling, David; Kunovac, Jelena
Abstract: Objective: Evaluate efficacy and safety of a 2-month dose of aripiprazole lauroxil (AL) with a 1-day initiation regimen during hospitalization for an acute exacerbation of schizophrenia. Methods: In the phase 3b double-blind ALPINE study, adults with schizophrenia were randomized to AL (AL NanoCrystal® Dispersion + oral aripiprazole 30 mg day 1; AL 1064 mg day 8 and every 8 weeks) or paliperidone palmitate (PP 234 mg day 1; PP 156 mg day 8 and every 4 weeks). Patients were discharged after 2 weeks of hospitalization and followed through week 25. Primary endpoint was within-group changes in PANSS total score from baseline to week 4 (observed cases). Secondary analyses included within-group changes at weeks 9 and 25 (observed) and between-group comparisons at weeks 4, 9, and 25 (MMRM). Adverse events (AEs) were monitored throughout the study. Results: 200 patients were randomized (AL, n=99; PP, n=101); 56.6% and 42.6%, respectively, completed the study. Within-group changes from baseline in PANSS were −17.4 for AL and −20.1 for PP at week 4 (both groups, P<0.001) and continued to decline at weeks 9 (AL, −19.8; PP, −22.5) and 25 (AL, −23.3; PP, −21.7). The change in PANSS over time was similar between groups. AEs occurring in ≥10% of patients in either group were injection site pain (AL, 17.2%; PP, 24.8%), akathisia (AL, 9.1%; PP, 10.9%), and weight increased (AL, 9.1%; PP, 16.8%). Conclusions: AL and PP were effective and well-tolerated for initiating treatment of schizophrenia in the hospital and continuing in the outpatient setting. Funding Acknowledgements: This study was funded by Alkermes, Inc.